Recent interdecadal changes in the interannual variability of precipitation and atmospheric circulation over northern Eurasia. (2nd June 2016) - Hiyama, Tetsuya; Fujinami, Hatsuki; Kanamori, Hironari; Ishige, Takaya; Oshima, Kazuhiro
Abstract: This study investigated the interannual variability and trends in precipitation and atmospheric circulation patterns over northern Eurasia using long-term Precipitation REConstruction over Land and atmospheric Japanese 55-year Reanalysis data (JRA-55) from 1958 to 2012. Special emphasis was placed on the recent increase in summer (June, July and August) precipitation around the Lena river basin in eastern Siberia. We found interdecadal modulation in the relationships between interannual variability in summer precipitation and atmospheric circulation patterns among the three major Siberian river basins (Lena, Yenisei, and Ob). The interannual variations in summer precipitation over the Ob and Lena river basins were negatively correlated from the mid-1970s to the mid-1990s. However, after the mid-1990s, this negative correlation became insignificant. In contrast, a significant positive correlation was apparent between the Yenisei and Lena river basins. We also found that there has been a significant increasing (positive) trend in geopotential height in the low-level troposphere since the mid-1980s over Mongolia and European Russia, resulting in an increasing trend of westerly moisture flux into the Yenisei and Lena river basins. Summer precipitation in both basins was continuously high from 2005 to 2008 under a trough that broadly extended from the Yenisei and Lena river basins, which has been a typical pattern of interannual variation since the mid-1990s. This trough increased the meridional pressure gradient between Mongolia and eastern Siberia in combination with the trend pattern. This further enhanced the eastward moisture flux towards the Lena river basin and its convergence over the basin, resulting in high summer precipitation from 2005 to 2008.